2020
DOI: 10.1177/0008125620931839
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mindsets: Recognizing and Leveraging Individual Beliefs for Digital Transformation

Abstract: Employees’ beliefs about technological change, their “digital mindsets,” are likely to influence their engagement in, or withdrawal from, their company’s digital transformation initiatives. Employees’ beliefs regarding the malleability of personal ability (fixed/growth mindset) and their beliefs about the availability of situational resources (zero-sum/expandable-sum mindset) influence the extent to which they see new technologies as providing opportunities for professional growth or as encroaching on their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 19 publications
7
97
0
4
Order By: Relevance
“…When it comes to the content of this cluster, we can observe that the concept of digital transformation (Berger et al, 2019; Nambisan et al, 2019; Verhoef et al, 2021) is usually adopted in relationship with a wide range of recently introduced enabling technologies such as AI, industrial internet of things, big data, and smart products (see Blackburn et al, 2017; Chandy et al, 2017; Farrington & Alizadeh, 2017; Fossen & Sorgner, 2019; Iansiti & Lakhani, 2014; Mariani & Fosso Wamba, 2020; Raff et al, 2020; Ransbotham et al, 2016; Sjödin et al, 2020; Verganti et al, 2020). Moreover, the studies included in the cluster offer evidence on service innovation (Sjödin et al, 2020), product‐service systems (Lerch & Gotsch, 2015), organizational practices and routines (Jackson, 2019), change management (Mugge et al, 2020; Solberg et al, 2020), innovation processes (Guenzi & Habel, 2020; Klein et al, 2020), competitive dynamics (Ferreira et al, 2019; Porter & Heppelmann, 2014, 2015), organizational design and structure (Kretschmer & Khashabi, 2020).…”
Section: Digital Transformation and Innovation Management: Opening Upmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to the content of this cluster, we can observe that the concept of digital transformation (Berger et al, 2019; Nambisan et al, 2019; Verhoef et al, 2021) is usually adopted in relationship with a wide range of recently introduced enabling technologies such as AI, industrial internet of things, big data, and smart products (see Blackburn et al, 2017; Chandy et al, 2017; Farrington & Alizadeh, 2017; Fossen & Sorgner, 2019; Iansiti & Lakhani, 2014; Mariani & Fosso Wamba, 2020; Raff et al, 2020; Ransbotham et al, 2016; Sjödin et al, 2020; Verganti et al, 2020). Moreover, the studies included in the cluster offer evidence on service innovation (Sjödin et al, 2020), product‐service systems (Lerch & Gotsch, 2015), organizational practices and routines (Jackson, 2019), change management (Mugge et al, 2020; Solberg et al, 2020), innovation processes (Guenzi & Habel, 2020; Klein et al, 2020), competitive dynamics (Ferreira et al, 2019; Porter & Heppelmann, 2014, 2015), organizational design and structure (Kretschmer & Khashabi, 2020).…”
Section: Digital Transformation and Innovation Management: Opening Upmentioning
confidence: 99%
“…The brown cluster includes studies focused on the central topic of innovation management (Gobble, 2018). These papers provide evidence about the impact of technological change (Wang et al, 2020) on employment, job creation, and disruptive innovation (Balsmeier & Woerter, 2019), adaptations of leadership styles, cognitive framings, and employee beliefs in accepting innovative technologies (Solberg et al, 2020).…”
Section: Digital Transformation and Innovation Management: Opening Upmentioning
confidence: 99%
“…the Corona crisis). Solberg et al (2020) showed that employees' digital mindsets may vary over time. The disruptive power of external shocks may have a pronounced effect on this foundation of innovation acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, IOL technologies that promote an ambidextrous working culture are crucial for organizational success. However, the implementation of IOL technologies such as Web-based IOL platform can only be successful when employees are willing to accept and use the technology (Mirow et al, 2008;Solberg et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation